Analysis of the distribution of urban services in unplanned areas (Case Study: District 9, Herat city, Afghanistan) - Pasoon Areffi; Jalil Ahmad Zakiri; Mohammad Yonus Wafa (Science and Education, 2024)
Cities today, especially in developing countries, in view of continuous population growth and urbanization, need more than any graduation period to focus on the establishment of spatial justice in the satisfaction of the needs of various urban services. Urban services in cities, and particularly in neighborhoods, play a crucial role in urban systems. Today, problems arising from the inadequate distribution of urban services have made urban service distribution a key element in the establishment of spatial justice. Faced with the rapid growth of Afghan cities, residents spontaneously, without government intervention, develop unplanned neighborhoods. The city of Herat, like most Afghan cities, has grown under the influence of the unusual expansion of urbanization in a non-regional and self-organized manner, and the assets of spaces are incomparable in dealing with urban services; therefore, the purpose of this study is to Analysis the distribution process of urban services for district 9th. The study used a qualitative research approach, semi-structural interviews, and spatial analysis to Analysis of the distribution of urban services in unplanned areas in the ninth district, the city of Herat. The results of the present survey indicate that urban service users do not follow the patterns of dispersion and equal access in the existing situation and in different neighborhoods, and in terms of access to urban services, they also have a deep gap with the practice of municipal services.